Ab-initio calculations of the structural, electronic and optical properties of (CdSe)2 clusters - Alselawe, A.I.A.; Jumali, MHH; Gopir, G.; M.M. Anas, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The distinctive properties of cadmium selenide (CdSe) semiconductor situated it in a multitudinous number of applications. Although (CdSe)2 cluster has more than one isomer, the previous studies concentrated merely on one isomer. The goal of this study was to determine the various stable geometric structure isomers of (CdSe)2 clusters; also, structural, electronic, and optical properties of the stable isomers are investigated using density functional theory (DFT). First, geometry optimization calculations of the possible geometric isomers were carried out using the BroydenFletcher-Goldfarb-Shanno minimization (BFGS) algorithm. Total ground-state energy calculations showed that all the converged isomers have a high probability of existing in any experiment, relying on the implemented experimental technique. Twenty initial possible geometric structures were investigated, in which eleven isomers were converged. However, all of them are relaxed in the 2D planar geometry. The results showed that eleven possible stable isomers were disclosed, where the final structures of the converged isomers produced six different structures; three of them were not detected before. The rhombus structure was ascertained to be the most stable isomer followed by the trapezoidal structure of (CdSe)2. The isomers’ Cd-Se bond length are 2.50-2.74 Å, and the average Cd-Se-Cd, Se-Cd-Se angles were 64.5o-123o and 56.3o-114.2o, respectively. Furthermore, the bond angles show that the selenium atom lone-pairs electrons are responsible for shifting the isomers’ structure from the linearity. The total ground-state energy differences were 0.00-1.82 eV. The calculated highest occupied molecular orbital (HOMO), and the lowest unoccupied molecular orbital (LUMO) gap of the isomers implied that the gap depends on the symmetrical geometry of the isomer. Furthermore, it was evident that the most stable isomers are accompanied with larger gaps. The HOMO-LUMO graphs demonstrated that HOMO orbitals were localized around the selenium atom, while LUMO orbitals were distributed around both cadmium and selenium atoms. The calculated absorption spectrum was unique for each isomer. The absorption edges for the isomers are ranging from 2.53 to 3.73 eV. The results show that the obtained absorption spectra peaks’ values (nm) are smaller compared to CdSe experimental results. (CdSe)2 clusters are very active that they straightforwardly react to produce larger clusters. Finally, the results of this study corroborate with previous computational studies.